Where the Place of Technology in Mathematics? - Fitriati, Fitriati (International Journal for Educational and Vocational Studies, 2019)
Technology integration in mathematics instruction is demanded throughout the educational system as it offers to support students achievement, teachers productivity, and effectiveness in classroom management. However, its implementation has presented some complex problems including lack of specific knowledge and skills of technological tools, diversity of points of view and beliefs, and the factor of time. This indicates that integrating technology to improve mathematics education is a challenging task. To ensure technology is used effectively to enhance students’ learning and teachers’ practice of mathematics, many facets need to be considered. Australian curriculum clearly mandated educational stakeholders to use technology to support daily mathematics instruction, but a direction of how to apply it in the classroom still unclear. It is suggested that more emphasis on rich mathematical tasks, productive pedagogies and developing teacher professional development that fosters both technological competence and pedagogy flexibility as proposed by many educational researchers is needed.